Chilli Pepper Extract (Capsicum frutescens L.) and Garlic (Allium sativum L.) as Repellents for Rice-Eating Birds in Pinrang Regency, South Sulawesi - Madani, Humairah; Priyambodo, Swastiko; Anwar, Ruly (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2026)
Grain-eating birds are one of the important pests that are the main factor in rice crop yield losses of up to 20-50%, therefore environmentally friendly control methods are needed. The study was conducted in rice fields using a randomized block design with four treatments and six replications, consisting of control, garlic (Allium sativum L.) extract, cayenne pepper (Capsicum frutescens L.) extract, and a combination of garlic and cayenne pepper extracts. The observed variables included bird population and species composition, crop damage intensity, and potential yield loss. The experiment used a randomized block design with four treatments and six replications, and the data were analyzed using analysis of variance, followed by Tukey’s test (α = 5%). The results showed that white-headed munia (Lonchura maja) and javan munia (Lonchura leucogastroides) were the most dominant bird species attacking rice crops. The application of botanical extracts was proven to reduce the level of bird presence in the research fields. Garlic extract showing the highest effectiveness and significantly different from the control, followed by chili cayenne extract and the combination of garlic and chili cayenne extracts. Bird presence in the fields was also influenced by the limited effectiveness of conventional control methods used by farmers and the presence of alternative host plants around the rice field area. Garlic and cayenne pepper repellent extracts are biologically effective and environmentally friendly, however they require repeated applications and are less economically efficient for a large scale application, indicating it is necessary to develop a more stable and cost effective botanical-based repellent formulations.